Search for single top quark production in p(p)over-bar collisions at root s=1.96 TeV in the missing transverse energy plus jets topology - Aaltonen, T; Adelman, J; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; et al. (2010)
We report a search for single top quark production with the CDF II detector using 2.1fb-1 of integrated luminosity of pp̄ collisions at √s=1.96TeV. The data selected consist of events characterized by large energy imbalance in the transverse plane and hadronic jets, and no identified electrons and muons, so the sample is enriched in W→τν decays. In order to suppress backgrounds, additional kinematic and topological requirements are imposed through a neural network, and at least one of the jets must be identified as a b quark jet. We measure an excess of signal-like events in agreement with the standard model prediction, but inconsistent with a model without single top quark production by 2.1 standard deviations (σ), with a median expected sensitivity of 1.4σ. Assuming a top quark mass of 175GeV/c2 and ascribing the excess to single top quark production, the cross section is measured to be 4.9-2.2+2.5(stat+syst)pb, consistent with measurements performed in independent data sets and with the standard model prediction. © 2010 The American Physical Society.